ANALISA BIAYA PEMBUKAAN LAHAN TANPA BAKAR DI DESA TELAGA LANGSAT KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Bambang Dwijanarko; Fonny Rianawati; Asysyifa Asysyifa (Jurnal Sylva Scienteae, 2020)
This study aims to find out what PLTB methods are carried out by the community, know the wage system, know the costs, know the most efficient method. The benefits of the research can provide information about methods, costs, wage systems and efficient PLTB methods so that it can be applied to the people of Telaga Langsat Village, Takisung District, Tanah Laut Regency. The basic method of this study uses descriptive methods, conducting direct interviews with the community regarding the cost components needed in land clearing without burning.The results of the research on PLTB activities are the manual method of piece rate wages, for an area of 35 borong or 1 ha, the average wage payment is Rp.36,000,-/borong and the average piece rate is Rp.1,260,000/ha. The manual method of PLTB costs daily wages, the average cost per person daily wage is Rp.75,667,-/day/person, the average daily consumption is Rp.10,000,-/person/day. The average daily wage costs Rp.1,553,000/ha. The cost of the manual method equipment is an average cost of Rp.166,564,-/person. The PLTB activity is a chemical method for piece rate wages, for an area of 35 borong or 1 ha, the average wage payment is Rp.5,617,-/borong, the average piece rate is Rp.196,583,-/ha. The PLTB chemical method costs daily wages, the average cost of a person's daily wage is Rp.61,500,-/day/person, the average daily consumption is Rp.10,000,-/person/day, the average daily wage costs are Rp.201,667,-/ha. The cost of equipment and chemical methods of chemistry on average per person costs Rp.480,033,-/person. the activity of the PLTB mechanical method of piece rate wages, for an area of 35 borong or 1 ha, the average wage payment is Rp.23,619,-/borong and the average piece rate is Rp.826,667,-/ha.